The concentration effects on structural and magnetic properties of Fe2V1-xMnxGe Heusler alloys - GÜLER, ADİL; BOYRAZ, CİHAT (My University, 2022)
This study presents the concentration-dependent structural, morphological, and magnetic properties of Fe2V1-xMnxGe Heusler alloys (x = 0.0, 0.25, and 0.50) have not been studied previously in the literature, and are investigated by using X-ray Diffractometer, Scanning Electron Microscope (SEM), and Physical Properties Measurement System (PPMS). We observed from the X-ray diffraction measurements that (except x = 0) Fe2V1-xMnxGe samples have had L2(1)-type crystal structure, matching well with the literature. In all SEM images, some holes and crack-type formations are observed. Increasing Mn content in Fe2V1-xMnxGe Heusler alloys can effectively inhibit grain boundary migration. Except for Fe2VGe, the other alloys in the series are investigated to be soft ferromagnets at 5 K with saturation magnetic moment. The (M-H) graphs especially for Fe2V0.75Mn0.25Ge and Fe2V0.5Mn0.5Ge measured at 5 K reveal almost no coercive fields and easy magnetization. Namely, the system easily saturates without needing any high fields. The obtained results show that these new samples may be suitable candidates for technological applications.
Keywords: Temel Bilimler; Natural Sciences; ÇOK DİSİPLİNLİ BİLİMLER; Doğa Bilimleri Genel; Temel Bilimler (SCI); MULTIDISCIPLINARY SCIENCES; NATURAL SCIENCES, GENERAL; Natural Sciences (SCI); Multidisipliner; Multidisciplinary; Heusler alloys; Sintering procedure; Structural and magnetic properties